2012
DOI: 10.4251/wjgo.v4.i12.250
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant crypt focus and fragile histidine triad protein in sporadic colorectal carcinoma

Abstract: AIM:To characterize aberrant crypt focus (ACF) in adjoining mucosa in sporadic colorectal carcinoma and to evaluate fragile histidine triad (Fhit) protein and Ki67.METHODS: ACF was identified grossly and classified histologically in 75 resected specimens. ACF was typed into hyperplastic ACF (HACF) and dysplastic ACF (DACF). Sections of ACF, carcinoma and normal colonic mucosa as control were studied for Fhit and Ki67 expressions by immunohistochemistry and were grouped according to staining intensity and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The present results indicated that reduced FHIT expression was frequent in serrated neoplasias, particularly SSA/Ps, when compared with non-serrated neoplasias. Aberrant crypt foci in the right side of the colon, one of the characteristics of MVHP, is a precursor lesion for the SSA/P-cancer sequence (29) and shows reduced FHIT expression (13,30). In the present study, reduced or no FHIT expression was detected in 30.8% of MVHPs.…”
Section: Discussionmentioning
confidence: 48%
“…The present results indicated that reduced FHIT expression was frequent in serrated neoplasias, particularly SSA/Ps, when compared with non-serrated neoplasias. Aberrant crypt foci in the right side of the colon, one of the characteristics of MVHP, is a precursor lesion for the SSA/P-cancer sequence (29) and shows reduced FHIT expression (13,30). In the present study, reduced or no FHIT expression was detected in 30.8% of MVHPs.…”
Section: Discussionmentioning
confidence: 48%